PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN PERTAMBANGAN - Ayu, Dea Putri; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2017)
The purpose of this study was to analyze : (1) The effect of profitability on CSR. (2) Effect of profitability and CSR on firm value. (3) The effect of the profitability on the firm value through CSR. Population studied is the mining company listed in the Indonesia Stock Exchange (BEI) 2010-2014. The sampling technique that used saturated sampling techniques and obtained as many as 24 companies with a total of 120 observations. This study using non-participant observation method taken from annual report and financial statement of companies. The analysis technique used is path analysis (path analysis). The results of this study are : (1) Profitability proven significant positive effect on CSR. (2) Profitability and CSR proven significant positive effect on firm value. (3) Profitability significantly positive effect on the value of the company through CSR. This syudy shows that CSR is able to mediate the effect of profitability on firm value.
Keywords: Profitability, Corporate Social Responsibility, Firm Values